Photovoltaic water pumping : a case study in Kwazulu - Gosnell, R J (Department of Chemical Engineering, 2023)
This is the first thorough evaluation of the viability and appropriateness of photovoltaic (PV) water pumping in South Africa. It is a case study of the operation of a PV water pumping system installed in a rural community vegetable garden in KwaZulu. The system comprised a 574 WP array, DC power maximizer, DC motor and a Mono (positive displacement) pump. The pump delivered an average of 15 m3 I day over a static head of 12.5 metres for a Standard Solar Day of 5 kWh/m2/d. Three facets were considered: technical, economic, and social. · For the technical evaluation the operation of the whole system as well as that of each component under various conditions were monitored in the field using a data logger. The economic evaluation compared the Life Cycle Costs of PV water pumping with those of diesel, petrol, and electric pumps. The social evaluation was based on three sets of interviews over a period of five years ranging from before the introduction of the pump to four years afterwards. The following are the most important conclusions. Technical: the system Daily Energy Efficiency was 2.22%. This is low in comparison with values given in Halcrow's authoritative report of 2.35% for their average systems and 3.28% for their best systems. The reason for this was the low efficiency of the Mono Pump: 39% in comparison with 41.5% for Halcrow's average systems and 59% for their best. This was because the head of 12.5 metres at Sondela was not ideal for the Mono Pump which is designed for 45 metres. All the low-cost PV pumping systems available in South Africa, however, use positive displacement pumps and are thus inefficient at low heads. But because PV pumps are more competitive economically at low heads and low flow rates, it is important that an efficient pump for these applications is designed. Submersible centrifugal pumps should be considered. · Economics: the applicability of various assumptions to developing areas has been thoroughly evaluated. This has laid U1e groundwork for a accurate computer program which would accurately compare the Life Cycle Costs of PV, diesel, petrol and electric pumps under a range of conditions. Connecting to the grid has many advantages and should be considered first. However, the costs of the normal tariff are affected strongly by the site and this option is out of the question for more remote sites. PV pumps are at the moment competitive with diesel pumps at only low hydraulic heads (around 40 m4/day). However, if a PV pump which was efficient at low heads were designed and if the path of the sun were physically tracked, then PV pumps could possibly be competitive up to hydraulic heads of 1400 m4/day. Social: the study showed that installing pumps in community vegetable gardens can almost double the productivity of the gardeners' time. The gardeners interviewed indicated that, because of the many advantages of PV pumps, they would prefer them to diesel pumps if their amortized costs were up to twice those of the diesel pump., But few, if any, community gardens would be able to raise the capital required for a PV pump. For this reason, a scheme similar to that just introduced by ESKOM could make a crucial difference to the marketability of PV pumps: ESKOM will buy and maintain the pump recovering the costs from the user at a fixed monthly rate stipulated before installation. This scheme obviates the two major barriers to the sale of PV pumps: I) high initial cost and ii) the risk of damage or loss of expensive equipment due to floods, theft, or vandalism.